ANALISIS PENGARUH PERILAKU KONSUMEN DALAM PENGAMBILAN KEPUTUSAN Studi Pembelian Rumah Sangat Sederhana Tipe 36 MeAlalui KPR – BTN di Kota Administrasi Jember - Sutrisno - Djaja; Agung - Yuniarinto; Agus - Suman (Wacana Journal of Social and Humanity Studies, 2010)
ABSTRACT This research aimed (1) at examining whether or not there was significant influence of the variables, such as marketing mix, reference group, demography and socioeconomic on the consumer’s behavior in deciding to purchase a house; and (2) at examining which variables have more dominant influence on the consumer’s decision making. The population of this research consisted of houses type 36 purchasers through the BTN Bank Credit in Jember. The sampling technique used was the purposive proportional area random sampling, whereas the data collecting methods used were questionnaire, interview and documentation. Marketing mix as an independent variable covered: product (X1), price (X2), place (X3), promotion (X4), personal traits (X5), physical evidence (X6) and process (X7). Reference group covered: family (X8), colleagues (X9) and neighbors (X10). Demography and Socio-economic was covered by Family Income (X11). The dependent variable (Y) was the decision making to purchase houses. The data analyses used were firstly, the descriptive analysis to describe the fieldwork data by interpreting the data through tabulation, and secondly, the multiple Linear Regression Statistics to analyze the influence of the independent variables (X1 – X11) both in group and individually on the decision making process to buy the houses. The research results indicated that marketing mix, reference group, and demography and socioeconomic constituted the variables to be considered and believed to influence the consumers’ decision-making process to buy the houses. The result of multiple linear regression analysis demonstrated that in a group marketing mix, reference group, demography and socioeconomic significantly affected the consumer’s behavior in deciding to buy houses. Individually, the dependent variables (X1-X11) significantly affected the dependent variables (Y), and certainly the product variable (X1) and the family income variable (X11) had dominant influence. Other variables served as the supporting variables.   Keywords: consumer behaviour, purchasing house